Handbook of modernity in South Asia : modern makeovers - Dube, Saurabh (New Delhi : Oxford University Press, 2011)
Contributed articles presented earlier at two conferences.
Includes bibliographical references.
Keywords: Social change -- South Asia -- Congresses; Civilization, Modern -- South Asia -- Congresses